2011
DOI: 10.1002/elan.201000758
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Glucose Oxidase to 3‐D Scaffolds of Carbon Nanotubes: Analytical Applications

Abstract: This study is the first to focus on the potential use of carbon nanotube (CNT) scaffolds as enzyme immobilization substrates for analytical purposes. Besides all the well-known advantages of CNT, three-dimensional scaffolds can significantly increase the amount of enzymes adsorbed per unit area, preserve the catalytic activity of the adsorbed molecules, and allow effective exposure to substrates present in the adjacent medium. Additionally, our results indicate that the sensitivity of analytical probes based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 75 publications
6
47
0
Order By: Relevance
“…In agreement with previous reports, MSE < 15 were considered acceptable. 45, 47 The ellipsometric measurements were interpreted using an optical model that considered the dielectric properties of Si (bulk, d = 1 mm) and SiO 2 (d = 2.1 ± 0.5 nm). A standard Cauchy function was added to describe the optical properties of the APTES layer (d = 0.89 ± 0.06 nm).…”
Section: Methodsmentioning
confidence: 99%
“…In agreement with previous reports, MSE < 15 were considered acceptable. 45, 47 The ellipsometric measurements were interpreted using an optical model that considered the dielectric properties of Si (bulk, d = 1 mm) and SiO 2 (d = 2.1 ± 0.5 nm). A standard Cauchy function was added to describe the optical properties of the APTES layer (d = 0.89 ± 0.06 nm).…”
Section: Methodsmentioning
confidence: 99%
“…Using a similar experimental set-up Nejadnik et al showed that in some cases, enzymes ( e.g. glucose oxidase) can be adsorbed to the interior of the CNT film, obtaining nanocomposites with higher catalytic activities [176] (see. These results support the hypothesis that adsorption can be effectively used to immobilize enzymes to the surface of CNT.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…This protein was selected as a convenient probe for the adsorption experiments because it allows an easy route to evaluate potential structural modifications affecting its catalytic activity. [16] Additionally, GOx is commercially available and has a well-characterized structure and activity. Therefore, the experiments herein presented describe the adsorption of GOx as a function of applied potential, solution pH, ionic strength, and enzyme concentration, as followed in real time by spectroscopic ellipsometry (SE).…”
Section: Introductionmentioning
confidence: 99%